TEMPORARY PLASTIC CROWNS IN PROSTHODONTIC DENTISTRY: CLINICAL AND MATERIAL ASPECTS OF MODERN PROVISIONAL RESTORATIONS - Nabieva Sevda (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   Temporary crowns are an essential component of fixed prosthodontic treatment, providing  protection  of  prepared  teeth,  maintenance  of  occlusal  function,  and preservation  of  aesthetic  appearance  during  the  interim  period  before  definitive prosthetic  restoration.  The  present  study  analyzes  clinical  and  material  aspects  of temporary  plastic  crowns,  including  their  fabrication  techniques,  biomaterial properties, and associated complications. Special attention is given to acrylic and bis-acrylic  resin  systems,  as  well  as  CAD/CAM-based  provisional  materials.  Clinical evaluation  indicates  that  bis-acrylic  materials  demonstrate  improved  mechanical strength, superior marginal adaptation, and enhanced aesthetic outcomes compared to conventional  acrylic  resins.  Proper  fabrication  protocols  significantly  reduce  the incidence of complications such as gingival inflammation, crown dislodgement, and marginal  leakage.  The  findings  confirm  the  clinical  importance  of  high-quality provisional restorations in achieving long-term success in fixed prosthodontic therapy.